Síntese e avaliação biológica dos compostos 3-triazoilcalcogeniltimidina - Sarturi, Joelma Menegazzi (2018)
This work describes the synthesis and antioxidant and antitumoral activity of 3-triazoylcalcogenylthymidine (7a-o). A variety of nucleoside analogues were prepared using a Huisgen 1,3-dipolar cycloaddition, between the azide group from ziduvudine 6 and the chalcogenoacetylenes (5a-n). The compounds (7a-o) were prepared via a partial convergent synthesis, involving a previously obtention of the respective chalcogenoacetylenes (5a-n) containing electron donating and withdrawing groups attached in the aryl ring from chalcogenium portion. The evaluation of some reaction parameters as catalyst, solvent and time was performed affording in the optimal reaction condition the respective nucleosides with yields ranging from 59 to 94%.